Cancer Care Delivery Research: Building the Evidence Base to Support Practice Change in Community Oncology - Kent, Erin E. (J Clin Oncol, 2015)
Understanding how health care system structures, processes, and available resources facilitate and/or hinder the delivery of quality cancer care is imperative, especially given the rapidly changing health care landscape. The emerging field of cancer care delivery research (CCDR) focuses on how organizational structures and processes, care delivery models, financing and reimbursement, health technologies, and health care provider and patient knowledge, attitudes, and behaviors influence cancer care quality, cost, and access and ultimately the health outcomes and well-being of patients and survivors. In this article, we describe attributes of CCDR, present examples of studies that illustrate those attributes, and discuss the potential impact of CCDR in addressing disparities in care. We conclude by emphasizing the need for collaborative research that links academic and community-based settings and serves simultaneously to accelerate the translation of CCDR results into practice. The National Cancer Institute recently launched its Community Oncology Research Program, which includes a focus on this area of research.